A ação monitória à luz do Código de Processo Civil de 2015 - Amaral, Rodrigo Augusto (2021)
This work intends to analyze the institute of the execution of an uneforceable instrument under the aegis of the new code of civil procedure, edited by Law 13.105, of March 16, 2015. The relevance of the theme lies in seeking to understand, after a previous historical and systemic digression of the institute, what it has evolved, regressed and what could have been better accommodated by the new civil procedural legal system. The work was developed after extensive national and international doctrinal research, as well as a study presented of judgments, especially from the Superior Court of Justice, issued under the Buzaid code and the current one. Another point of great relevance was to indicate that the monitoring action in the Brazilian legal system continues to be exclusively documentary, but with an updated rereading of what must be taken as written evidence. Also, in this work it was possible to analyze and conclude that, currently, it is impossible not to conclude that the execution of an uneforceable instrument admits to be proposed even if accompanied by an extrajudicial executive title. The result obtained was demonstrated, indicating some concrete advances that the execution of an uneforceable instrument currently allows, with an expansion of its object, legitimacy, as well as a deeper regulation of the subject. From an institute that was doomed to be removed from the legal system by the draft reform of the Federal Senate, the execution of an uneforceable instrument was revived, updated and, thus, studied